Vaccinating the future: Parental acceptance towards COVID-19 vaccination in children aged 6-11 years in Indonesia through the Health Belief Model - Nurul Mardiati; Liana Fitriani Hasymi; Ikhwan Yuda Kusuma; Ratih Puspita Kusumadewi Purba; Rizal Rizal; Imam Jayanto (GarVal Editorial Ltda., 2023)
Context: The current study focuses on the acceptability of COVID-19 vaccines among parents of children aged 6-11 years, based on a review of the Health Belief Model (HBM) behavioral theory, Indonesia. Aims: To investigate the acceptability of COVID-19 vaccines among parents of children aged 6-11 years in Indonesia based on a review of the HBM behavioral theory. Methods: A national, cross-sectional was conducted in June-August 2022. The self-administered online questionnaire was distributed to a random sample of 400 parents. Results: A total of 400 participants completed the questionnaire, of whom 87.3% received vaccination for their 6-11 years old children. Participants who had adequate information about the COVID-19 vaccine (OR = 27.543; Cl 95% =3.514-215.901) were among the most amenable to vaccinating their children. The results indicated that the HBM construct explained 83.9% (R square = 0.839) of the acceptance of COVID-19 vaccination. However, there are still some parents who reject vaccines due to lack of information, on parental knowledge of vaccine adverse events, and sources of information used by parents, among others. Conclusions: Parents of children aged 6-11 years old in Indonesia are accepting to receive COVID-19 vaccinations. However, there are still some parents who refuse vaccines. The urge to act construct contributed significantly to the vaccine acceptance variable, and those who had received enough information about the COVID-19 vaccine were more amenable. Therefore, the government of the Republic of Indonesia's efforts must be directed toward increasing parents' vaccine awareness and tackling the constructs of the Health Belief Model through a well-designed vaccination campaign.